Design Development of Food & Beverage Product Packaging for SMES co in Java and West Nusa Tenggara, Economic Corridor. - Agus Windharto (Institut Teknologi Sepuluh Nopember, 2014)
Population of Food & Beverage SME's Co in Indonesia reached 38 % of total 52 million SMEs, equivalent to 19.76 million SMEs. Indonesian Consumption reached Rp997 trillion in 2012 and its 27 % is in the form of processed foods that packed (Rp296, 19 trillion). Expenditure of industrial packaging products for SME are big, worth 5 % of whole packaging product price that equivalent to Rp13, 46 trillion. SMEs Contribution (21 % worth of 19.76 million) is still relatively considered small competitive to Indonesian market from those of medium and large industrial supply both for local and abroad (79 %). The main issue is Food & Beverage SMEs Competitiveness products relatively low, lack of promotion, weak brand, packaging design not meet good standards and food quality below safety standards. The purpose of this research is to improve the competitiveness of food and beverage SMEs Co through capacity building, took places on some